2020
DOI: 10.1177/1535370220975106
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates alveolar epithelial cell injury induced by hyperoxia by reducing apoptosis and mitochondrial dysfunction

Abstract: Bronchopulmonary dysplasia is a severe and long-term pulmonary disease in premature infants. Hyperoxia-induced acute lung injury plays a critical role in bronchopulmonary dysplasia. Resveratrol is a polyphenolic phytoalexin and a natural agonist of Sirtuin 1. Many studies have shown that resveratrol has a protective effect on hyperoxia-induced lung damage, but its specific protective mechanism is still not clear. Further exploration of the possible protective mechanism of resveratrol was the main goal of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Studies have shown that the clinical drugs used to improve breathing, such as aminophylline and montelukast, can promote the biogenesis of human alveolar epithelium mitochondria through cAMP responsive element binding protein (CREB)/PGC-1α (Wang et al, 2019;Wei et al, 2019). The use of the mitochondrial antioxidant resveratrol can protect mtDNA and reduce apoptosis through SIRT1-PGC-1a (Wang et al, 2020;Zhu et al, 2021). These findings suggest that the biogenesis of mitochondria plays an important role in protecting against hyperoxic lung injuries.…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…Studies have shown that the clinical drugs used to improve breathing, such as aminophylline and montelukast, can promote the biogenesis of human alveolar epithelium mitochondria through cAMP responsive element binding protein (CREB)/PGC-1α (Wang et al, 2019;Wei et al, 2019). The use of the mitochondrial antioxidant resveratrol can protect mtDNA and reduce apoptosis through SIRT1-PGC-1a (Wang et al, 2020;Zhu et al, 2021). These findings suggest that the biogenesis of mitochondria plays an important role in protecting against hyperoxic lung injuries.…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…Notably, our previous study showed that Res reduced hyperoxia-induced apoptosis and mitochondrial dysfunction in alveolar epithelial cells through the activation of SIRT1/PGC-1α. 22 Hence, the aim of this study was to establish a neonatal rat model of BPD to verify whether Res attenuates hyperoxia-induced lung injury through the SIRT1/PGC-1α signaling pathway.…”
mentioning
confidence: 99%
“…The beneficial effects of RSV on cisplatin-induced oxidative stress, inflammation, and apoptosis in female rats' ovarian and uterine tissues have been discovered ( 55 ). RSV may alleviate hyperoxia-induced mitochondrial dysfunction and apoptosis in alveolar epithelial cells through the SIRT1/PGC-1α signaling pathway ( 56 ). Interestingly, in the present study, NT + RSV markedly decreased the relative gene expression of BAX compared with the NT group.…”
Section: Discussionmentioning
confidence: 99%